Tourism-Service Language: A Cross-Cultural Perspective on Politeness - Budi Purnomo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
This research aims at analyzing politeness principles, politeness norms and cross-cultural perspectives on politeness in tourism-service language used by tourism industry practitioners in Central Java. The research findings indicate that tourism industry practitioners in Central Java use various politeness principles and norms in serving English speaking tourists, Indonesian speaking tourists and Javanese speaking tourists. The findings also indicate that there are similar and different perspectives on politeness among English speaking tourists whose backgrounds are Western cultures, Indonesian speaking tourists whose backgrounds are Indonesian cultures and Javanese speaking tourists whose backgrounds are Javanese cultures towards the tourism-service language used by tourism industry practitioners in Central Java.